Automorphisms of Kronrod-Reeb graphs of Morse functions on 2-torus - Kravchenko, A.; Feshchenko, B. (Methods of Functional Analysis and Topology, 2020)
This paper is devoted to a study of special subgroups of automorphism groups of Kronrod-Reeb graphs of Morse functions on 2-torus T^2 which arise from actions of diffeomorphisms preserving a given Morse function on T^2. In this paper we give a full description of such classes of groups.